2019
DOI: 10.1002/pon.5128
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychological experiences in allogeneic hematopoietic stem cell transplantation

Abstract: Objective Positive psychological constructs (e.g., optimism and hope) have been associated with superior health outcomes in the recovery from hematopoietic stem cell transplantation (HSCT) in prior work. However, such studies have not examined a broad range of positive psychological constructs, their sources or evolution over time, or their connections with key health behaviors. We used semistructured qualitative interviews in 25 HSCT patients to explore the nature and sources of positive psychological experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…HSCT is marked by expectations of a successful procedure, in which optimism and hope are very important. In the research (22) carried out with adult patients for allogeneic transplantation during hospitalization and approximately 100 days after the procedure, the results showed positive psychological constructs, especially gratitude, determination and optimism. According to the study mentioned, in the beginning, the participants reported thankfulness for their donors and, afterward, hope for a cure was prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT is marked by expectations of a successful procedure, in which optimism and hope are very important. In the research (22) carried out with adult patients for allogeneic transplantation during hospitalization and approximately 100 days after the procedure, the results showed positive psychological constructs, especially gratitude, determination and optimism. According to the study mentioned, in the beginning, the participants reported thankfulness for their donors and, afterward, hope for a cure was prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Bir çalışmada, naklin donör ile alıcı arasında şükran ve hayranlıkla karakterize edilen özel bir bağ oluşturduğu, ancak aynı zamanda alıcının yaşam tarzına ilişkin yeni beklentileri de ortaya çıkardığı görülmüştür (Thys 2015). Bir başka çalışmada, katılımcıların sürekli olarak bağışçılarına minnettarlık bildirdikleri belirtilmiştir (Amonoo 2019). Kadavra nakli alıcıları üzerinde yapılan çalışmalarda da benzer sonuçlar bulunmuştur (Kamran ve Ogden 2016, Dicks ve ark.…”
Section: Discussionunclassified
“…We have previously reported full details about study design, procedures and analysis (Amonoo, Brown, et al., 2019) and include brief details below. We used a qualitative research design and hour‐long, semi‐structured qualitative interviews to explore the negative emotional experiences of HSCT patients in the first 100 days of transplantation.…”
Section: Methodsmentioning
confidence: 99%